Nuevos registros de escarabajos coprófagos (coleoptera: scarabaeidae: scarabaeinae) para el departamento de chocó (Colombia) - Arias-Buriticá, Jorge Armando; Delgado-Gómez, Paola; González-A, Fabio Arturo; Vaz-de-Mello, Fernando Zagury (Instituto de Ecología, A.C., 2011)
We present nine new records for dung beetles (Coleoptera: Scarabaeidae: Scarabaeinae) for the department of Chocó (Colombia): Ateuchus aeneomicans, Canthon juvencus, C. cyanellus, Onthophagus coscineus, O. marginicollis, Sulcophanaeus miyashitai metallescens, Ateuchus candezei, Dichotomius favi and Uroxys platypyga also the last three being new records for Colombia, as well as expand the distribution of the same to South America.